Pengaruh Pemakaian Jenis Bahan Bakar Terhadap Kinerja Boiler dengan Metode Langsung dan Tidak Langsung - Nahda Alifa Zahira Putri; Ika Yuliani; Sri Widarti (SURYA TEKNIKA, 2024)
Boilers produce steam by heating water using heat energy from burning fuel. This research analyzes the effect of fuel type on the performance of the 52-B-101C boiler at PT Kilang Pertamina Internasional RU VI Balongan. The performance parameters calculated are the evaporation ratio and efficiency using direct and indirect methods according to ASME Standard: PTC 4-1. The research results show that the use of 50% and 100% natural gas produces an evaporation ratio of 13,166 and 19,911, direct efficiency of 67.113% and 86.893%, and indirect efficiency of 87.699% and 85.758%. In conclusion, the use of 100% natural gas provides better boiler efficiency and performance. It is recommended to reduce the use of atmospheric residue and increase the use of natural gas with a hydrogen content that is not too high.